Procedural Justice and Police Legitimacy: Untangling the Effects of Racial and Ethnic Combinations Between the Police and Civilians - Li, Luye (Criminal justice review, 2025)
In the 21st century, law enforcement agencies have increasingly realized the importance of police–civilian contacts in shaping public evaluations of legal authorities. Although many studies have revealed the Black–White racial disparities in public perceptions of the police, the impact of the nexus of civilian and officer race and ethnicity has rarely been adequately examined. Drawing upon a nationwide dataset, this study examined the effects of racial and ethnic combinations between the police and civilians on attitudes toward procedural justice and police legitimacy reported by 5,201 civilians who had recent encounters with police officers during traffic or pedestrian stops. The results showed a perception disparity regarding procedural justice and legitimacy among racial/ethnic combinations involving White, Black, and Hispanic civilians and officers. The nexus of Black-civilians–White-officers yielded the most negative effect. Hispanic civilians displayed more positive attitudes toward the police than their White counterparts. Procedural justice mediated the racial/ethnic effect on the perception of police legitimacy. Findings and policy implications are discussed.